2019
DOI: 10.3390/en12193797
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on the Effect of Interfacial Heat Transfer on Performance of Thermoelectric Generators

Abstract: The application of thermoelectric generator (TEG) systems in waste heat recovery has attracted more and more attention. In this work, the effect of interfacial heat transfer on the performance of TEG module was experimentally and numerically investigated. Three kinds of thermal greases with thermal conductivities of 2.0, 2.5, and 3.0 W/(m∙K) were used as thermal interface materials (TIMs) to improve interfacial heat transfer at different external pressures ranging from 0.1 to 0.4 MPa. The open-circuit voltage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
0
7
0
14
Order By: Relevance
“…Nowadays, more suitable thermal interface materials (TIM) are used to improve the operation performance of TE modules in different locations and working conditions. These include inorganic compounds [162], greases [163], graphite [164], metal nanometer material [165], and carbon materials. The results [153] showed that the boron nitride-based ceramic coating, white coating and polyurethane-based sheet are suitable for reducing contact resistance, respectively.…”
Section: Extrinsic Factors: Contact Resistancementioning
confidence: 99%
“…Nowadays, more suitable thermal interface materials (TIM) are used to improve the operation performance of TE modules in different locations and working conditions. These include inorganic compounds [162], greases [163], graphite [164], metal nanometer material [165], and carbon materials. The results [153] showed that the boron nitride-based ceramic coating, white coating and polyurethane-based sheet are suitable for reducing contact resistance, respectively.…”
Section: Extrinsic Factors: Contact Resistancementioning
confidence: 99%
“…Bu nedenle son yıllarda TIM'lerin bir TEJ sistemine uygulanması çalışmaları artan bir ilgiye sahiptir. Ancak bu konudaki çalışmalar hala sınırlı sayıdadır [26][27][28][29]. Wang vd.…”
Section: Introductionunclassified
“…Finite time thermodynamics (FTT) [1][2][3][4][5][6][7][8][9][10][11][12][13] has been applied to perform performance analyses and optimizations for various thermodynamic cycles and processes, including multi-stream heat exchange system [14], chemical reactors [15][16][17][18], electrochemical device [19], biological process [20], Novikov engines [21][22][23], Agrawal engine [24], Carnot engines [25,26], solar engine [27], internal combustion engine cycles [28][29][30][31][32], thermoelectric devices [33][34][35][36], cogeneration plants [37][38][39], ocean thermal energy conversion plants [40][41][42], Kalina cycle [43], Rankine cycles [44][45][46], Brayton cycles [47]…”
Section: Introductionmentioning
confidence: 99%